The Effect of Traditional Opposition Games on University Students' Mood States: The Score and Group Type as Key Aspects - Cifo Izquierdo, María Isabel; Alcaraz-Muñoz, Verónica; Gea-García, Gemma Maria; Yuste-Lucas, Juan Luis; Alonso Roque, José Ignacio (Frontiers in Psychology, 2021)
Playing traditional games has a direct impact on the mood states of the players, and this is the reason why physical education is an ideal setting for teaching how to recognize them and be aware about how they can swing. The objective of the study was to determine if participating in traditional opposition games causes changes to the participants’ mood states. A total of 102 students participated. Each participant recorded the intensity of the mood state experienced at the beginning and at the end of the sessions, using the validated Profile of Mood States (POMS) instrument. The pedagogical experience was planned as 4 sessions with 6 and 5 opposition games each: a) with competition in mixed groups, equally and unequally mixed; b) without competition in mixed groups, equally and unequally mixed; c) with competition in same-gender groups; and d) without competition in same-gender groups. When comparing the different mood states according to session (with or without competition), the mood states of the depression, fatigue, and vigor dimensions were significantly different (p<0.05), with higher scores in the sessions with competition for the mood states of vigor (Mcompetition=7.27 and Mno_competition=3.10) and fatigue (Mcompetition=4.08 and Mno_competition=1.80). Also, when comparing the mood states depending on session grouping and group type, the results showed differences in the scores obtained for the dimensions fatigue and anger, and general mood state (p<0.05). These differences were found at the start of the session and at the end, with the dimension fatigue being the only one with differences in both situations when comparing the same-gender, equally-mixed, and unequally-mixed groups for the two types of traditional opposition games compared. In addition, after an analysis of the mood states depending on gender was performed, the results and therefore the significant differences found, were very similar to those obtained according to group type. Lastly, it was concluded that the type of group (equal, mixed & same gender), and gender were decisive, causing variations in the mood states of the students. This provides valuable information for teaching professionals about the structuring and organization of PE sessions, aiming to promoting positive motor experiences.